Mining of data of the comprehensive evaluation of the academic performance of the leveling unit - Uvidia Fassler, María Isabel; Viñán Carrera, Javier Alonso; Cisneros Barahona, Andrés Santiago (mktDESCUBRE, 2017)
The Ecuadorian universities during the last years have handled a number of processes, being the integral evaluation to the important and delicate educational performance. Facing this situation, the Standard Admissions Center (UNAE) of the Escuela Superior Politécnica de Chimborazo (ESPOCH), through the application of knowledge discovery in Databases (KDD), generated a methodological proposal adapted with the academic unit requirements, called the KDD - ESPOCH methodology, which allowed the generation of a data warehouse (DW) with consistent academic information. For this analysis, the data of the integral evaluations of the teachers of the UNAE are considered; (Data Mining - DM), decision trees and Bayesian networks, as part of the KDD methodology, schemas were generated with optimal percentages of reliability and precision, which allowed to know the performance of the academic activity and participation of teachers of this department by gender in the different areas of knowledge and by academic periods. Furthermore, to establish patterns and possible integral evaluation trends. Finally, the purpose was to identify the areas of knowledge in the UNAE courses with the academic offer of the university, in which academic and administrative strengthening strategies should be implemented that allow a positive impact on the teaching - learning process.